Impact of direct-acting antivirals on neuropsychiatric and neurocognitive dysfunction in chronic hepatitis C patients - Ghaydaa A. Shehata; Gellan K. Ahmed; Elham Ahmed Hassan; Abeer Sharaf El-Din Abdel Rehim; Saad Zaky Mahmoud; Noha Ali Masoud; Gehan S. Seifeldein; Waleed Attia Hassan; Khaled O. Aboshaera (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Hepatitis C virus (HCV) infection is associated with psychiatric and cognitive dysfunctions. We aimed to investigate depression, anxiety, and cognitive function of chronic hepatitis C (CHC) patients before and after treatment with direct-acting antivirals (DAAs). Forty CHC patients (20 non-cirrhotic and 20 cirrhotic) who had undergone DAA treatment in our outpatient clinic and ten controls. We administered the Hospital Anxiety and Depression questionnaires to measure the anxiety and depression symptoms and the Cognitive Abilities Screening Instruments (CASI) to measure the cognitive function at the beginning and 3 months after the end of the treatment. Results Sustained virological response (SVR) was achieved in all patients. Post-treatment anxiety and depression scores showed a significant improvement than pre-treatment ones in CHC patients. Regarding CASI, before and after the treatment, a statistical significance was found in short-term memory (P = 0.001), concentration (P = 0.033), abstract thinking and judgment (P = 0.024), total (P = 0.001) in non-cirrhotic, Also, an improvement was seen in long-term memory (P = 0.015), short-term memory (P < 0.001), concentration (P = 0.024) and total (P = 0.01) in cirrhotic. However, these changes were still impaired in post-treated cirrhotic compared to controls. Conclusions CHC patients' anxiety, depression, and cognitive function partially improved after DAA therapy. Besides, improving the status of CHC, reversibility of cognitive dysfunction in non-cirrhotic patients may indicate the importance of treatment in early stages of liver disease.